Cardiovascular disease in type 2 diabetes mellitus: Relationship between microalbuminuria and cardiovascular risk factors - Koksalan, Damla; Sozen, Mehmet; Solmaz, Kubra; Altunoglu, Esma (Annals of Medical Research, 2021)
Aim: In this study, the relationship between cardiovascular disease (CVD) risk factors and microalbuminuria (MAU) in patients with type 2 diabetes mellitus (DM) was investigated.Materials and Methods: The data of type 2 DM patients without CVD were evaluated retrospectively. Anthropometric measurements were made using calibrated standard devices. Biochemical data of the patients were obtained from the hospital information processing system. Patients with type 1 DM, history of CVD and diseases that may affect the MAU level were excluded from the study. Statistical analysis was done using SPSS 22.0.Results: The study included 300 type 2 DM patients with the mean age of 58.9±10.1. 56.7% of the cases (n=170) were female, and 43.3% (n=130) were male. 12.7% of the cases were obese (BMI>30 kg/m2). Body mass index, blood pressure (BP), LDL, glycated hemoglobin (HbA1c) and lipoprotein (a) levels were detected to be higher in patients with MAU (p
Keywords: Diabetes mellitus; lipoprotein (a); microalbuminuria; risk factor